Fatal acute undifferentiated febrile illness among clinically suspected leptospirosis cases in Colombia, 2016-2019. - Eliana L Parra Barrera; Jhonatan Reales-González; Daniela Salas; Elizabeth Reyes Santamaría; Solmara Bello; Angélica Rico; Lissethe Pardo; Edgar Parra; Karina Rodriguez; Zonía Alarcon; Angela Patricia Guerra Vega; Mayra A Porras; et al. (Public Library of Science (PLoS), 2023)
Background Acute undifferentiated febrile illness is a common challenge for clinicians, especially in tropical and subtropical countries. Incorrect or delayed diagnosis of febrile patients may result in medical complications or preventable deaths. Common causes of acute undifferentiated febrile illness in Colombia include leptospirosis, rickettsioses, dengue fever, malaria, chikungunya, and Zika virus infection. In this study, we described the acute undifferentiated febrile illness in postmortem patients reported as suspected cases of leptospirosis through the national leptospirosis surveillance in Colombia, 2016-2019. Methodology/principal findings We retrospectively analyze human fresh and formalin-fixed tissue samples from fatal suspected leptospirosis cases reported by the Public Health Laboratories in Colombia. Leptospirosis confirmation was made by immunohistochemistry, real-time polymerase chain reaction (PCR) in the tissue samples. In some cases, the serum sample was used for confirmation by Microagglutination test (MAT). Simultaneously, tissue samples were tested by PCR for the most common viral (dengue, Zika, and chikungunya), bacterial (Brucella spp., and Rickettsia spp.), and parasitic (malaria). Fresh tissue samples from 92 fatal suspected leptospirosis cases were reported to the National Reference Laboratory from 22/32 departments in Colombia. We confirmed leptospirosis in 27% (25/92) of cases. Other pathogens identified by real-time PCR were Brucella spp. (10.9%), Rickettsia spp. (14.1%), and dengue (2.2%). Dengue (6.9%), hepatitis (3.5%), and Yellow Fever cases (2.2%) were detected by the pathology. All patients were negative for chikungunya and Plasmodium spp. Most cases were classified as undifferentiated febrile illnesses (45.7%; 42/92). Conclusions/significance This study underscores the importance of early and accurate recognition of leptospirosis to prevent mortalities. Moreover, it draws attention to the existence of other febrile syndromes in Colombia, including rickettsiosis and brucellosis, that currently lack sufficient human surveillance and regular reporting. Expanding laboratory surveillance to include viruses such as Hantavirus, Mayaro virus, Oropouche virus, and West Nile virus is crucial.